Adaptation Strategies of Smallholder Tobacco Farmers in Bojonegoro in Response to Climate Variability and the Economic Crisis, 1996–2000 - Sintia Nofita Anggraini; Hieronymus Purwanta (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study examines the adaptation strategies adopted by smallholder tobacco farmers in Bojonegoro in response to climate variability and the economic pressures of the 1997–1998 economic crisis during 1996–2000. It addresses the limited historical research on the interaction between climate variability and economic crises in shaping tobacco farming. Using a historical method with a socio-economic approach, the study applied heuristics, source criticism, interpretation, and historiography. Data were obtained from statistical archives of Statistics Indonesia (BPS), archives of the Indonesian Sweetener and Fiber Crops Research Institute (Balittas), and interviews with tobacco farmers in Bojonegoro. The findings show that the 1997 El Nino, the 1998–2000 La Nina phenomena, and rising production costs during the economic crisis created significant challenges for tobacco farming. Farmers responded by selecting productive land, adjusting cultivated areas, and diversifying crops according to seasonal conditions and economic constraints. These strategies reduced production risks and supported household livelihoods. The study concludes that the sustainability of tobacco farming in Bojonegoro was largely determined by farmers' adaptive capacity in responding to environmental and economic change.